INTERNATIONAL ORGANIZATIONS AND THEIR ROLE IN GLOBAL GOVERNANCE - Enazarova Dilnoza Ravshanjonovna, (Ustozlar uchun, 2025)
Annotation:This scientific article discusses the significance and role of international organizations in maintaining peace, ensuring human rights, promoting economic development, and strengthening international cooperation. It examines both intergovernmental and non-governmental organizations, including the United Nations, the World Trade Organization, and the International Monetary Fund, highlighting their impact and challenges in the context of global governance. The study concludes that international organizations are indispensable for resolving transnational issues and fostering diplomatic collaboration in the modern world.